1977
DOI: 10.2134/jeq1977.00472425000600010022x
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphorus Status of Eutrophic Lake Sediments as Related to Changes in Limnological Conditions—Phosphorus Mineral Components

Abstract: Studies of the relationship between limnological factors and changes in the P status of noncalcareous sediments of a eutrophic lake previously indicated that changes in sediment inorganic P were directly related to the biological productivity of the surface waters. This relationship was particularly pronounced in a shallow bay where sediment P decreased with lake phytoplankton growth and increased with their decline. The present studies were undertaken to identify the inorganic P components responsible for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…Depending on the strength of the extracting solution and the fractionation method, bioavailable P has been estimated from such extracts as: 1 M NH 4 Cl (Hieltjes and Lijklema, 1980;van Eck, 1982), 1 M KCl (Reddy et al, 1995a), 0.1 M NaOH (Wildung et al, 1977;Hieltjes and Lijklema, 1980;Ostrofsky, 1987), citrate-bicarbonate-dithionite , and nitrolotriacetic acid (NTA) (Golterman et al, 1969;Gunatilaka et al, 1988). The Ca-bound P (HCl-RP) such as apatite was found to be unavailable (Pettersson, 1986;Gunatilaka, 1988), while the redox-sensitive Fe-bound P may become available under anaerobic conditions (Wildung et al, 1977;Furumai and Ohgaki, 1982;Hosomi et al, 1981).…”
Section: Forms Of Soil and Sediment Phosphorusmentioning
confidence: 99%
“…Depending on the strength of the extracting solution and the fractionation method, bioavailable P has been estimated from such extracts as: 1 M NH 4 Cl (Hieltjes and Lijklema, 1980;van Eck, 1982), 1 M KCl (Reddy et al, 1995a), 0.1 M NaOH (Wildung et al, 1977;Hieltjes and Lijklema, 1980;Ostrofsky, 1987), citrate-bicarbonate-dithionite , and nitrolotriacetic acid (NTA) (Golterman et al, 1969;Gunatilaka et al, 1988). The Ca-bound P (HCl-RP) such as apatite was found to be unavailable (Pettersson, 1986;Gunatilaka, 1988), while the redox-sensitive Fe-bound P may become available under anaerobic conditions (Wildung et al, 1977;Furumai and Ohgaki, 1982;Hosomi et al, 1981).…”
Section: Forms Of Soil and Sediment Phosphorusmentioning
confidence: 99%
“…Phosphorus removed by the first one or two extracting solutions in a sequential fractionation method is usually considered readily available (Gunatilaka, 1988 ;Psenner et al, 1988) . Depending on strength of extracting solution and fractionation method, readily available P has been estimated from such extracts as : 1 M NH4C1 (Hieltjes & Lijklema, 1980 ;van Eck, 1982), 0 .1 M NaOH (Wildung et al, 1977 ;Hieltjes & Lijklema, 1980 ;Ostrofsky, 1987), citrate-bicarbonatedithionite (Williams et al, 1971), and nitrolotriacetic acid (NTA) (Golterman et al, 1969 ;Gunatilaka et al, 1988) . The Ca-bound P (HCl-P) such as apatite was found to be unavailable (Pettersson, 1986 ;Gunatilaka, 1988), while the redox-sensitive Fe-bound P (NaOH-P) may become available under anaerobic conditions (Wildung et al, 1977 ;Furumai & Ohgaki, 1982 ;Hosomi et al, 1981) .…”
Section: Introductionmentioning
confidence: 99%
“…Chemical characterization of sediment P in eutrophic lakes provides information on the distribution of various P forms and their potential mobility and bioavailability under prevailing redox potential (Eh) and pH. Lake systems dominated by Fe-bound P, for example, are predicted to release P under anaerobic conditions (Wildung et al, 1977 ;Hosomi et al, 1981) . Similarly, P solubility in lake systems dominated by Ca-bound P are sensitive to changes in pH .…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study with lake sediment, Nalewajko and Lean (1978) observed that during early exponential growth of algae the influx of P from different sources might be less than total P uptake. Wildung et al (1977) also observed such a change in different forms of sediment-P which could be related to P uptake by expanding algal communities. The results, therefore, indicate that cyanobacteria might be able to solubilize P from these difficulty available forms in soils (Brady, 1990) and assimilate it during their growth.…”
Section: Discussionmentioning
confidence: 67%
“…Growth of cyanobacteria caused a small decrease, which is controversial in view of the fact that growth of cyanobacteria provides a more aerobic environment in soil due to release of photosynthetic 0 2. Wildung et al (1977) observed a decrease in citrate-bicarbonate-dithionite (CBD)-extractable P (considered to be reductant-soluble Fe-P) in lake sediments and suggested such phosphates to be an important source of P for algae, while Lee et al (1980) were of the opinion that P adsorbed onto hydrated oxides of Fe was unavailable for supporting algal growth.…”
Section: Discussionmentioning
confidence: 99%